Cost Allocation and Opportunity Costs - Miller, Bruce L.; Buckman, A. G. (Management Science, 1987)
One explanation for the widespread use of allocated fixed costs is that they can serve as a proxy for difficult-to-calculate opportunity costs. This explanation is pursued by modeling a service department as an M/M/s/s queueing system. Two main results are that the expected value of opportunity costs equals both the incremental productivity of capacity and the optimal transfer price. When the cost of capacity is of the form C(s) = as α and α is close to one, we show that allocated fixed costs are a good proxy for average opportunity costs. However, if there are great economies of scale (α is close to zero), then a method which charges users only for the variable costs of the service department is recommended. Finally, the economic efficiency of transfer prices based on either variable cost or full cost is compared with optimal transfer pricing policies.